2015 IEEE International Conference on Industrial Technology (ICIT) 2015
DOI: 10.1109/icit.2015.7125159
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of discrete-time models for model predictive control of induction motor drives

Abstract: System modeling and variables estimation are two important task in direct control strategies. In those schemes, the system performance is strongly related with the accuracy of the discrete-time model, especially for time-varying systems, e.g., high-performance motor drive applications. This investigation presents a numerical comparison between several discrete-time models of the induction machine (IM) used in model predictive control (MPC) schemes. The accuracy of each model is evaluated numerically for differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…The equations for the matrices describing this affine PMSM model are the basis for the discretisation step. As discussed later, simulations showed that discretisation with Euler approximation is not sufficient, which is in accordance with [11, 12]. The system was discretised with a third‐order Picard Iteration [13] to provide remedy to that problem.…”
Section: Modelling Of the Pmsmmentioning
confidence: 60%
“…The equations for the matrices describing this affine PMSM model are the basis for the discretisation step. As discussed later, simulations showed that discretisation with Euler approximation is not sufficient, which is in accordance with [11, 12]. The system was discretised with a third‐order Picard Iteration [13] to provide remedy to that problem.…”
Section: Modelling Of the Pmsmmentioning
confidence: 60%
“…2) Discretization: In accordance with [31] and [32] simulations show that a discretization with Euler Approximation is not reasonable for higher angular velocities ω el . The system was discretized with a third order Picard Iteration [33].…”
Section: B Affine State Space Modelmentioning
confidence: 79%
“…where the superscript 'P' denotes the predicted quantities and T s is the sampling interval. Although the zero-order-hold discretisation approximated by matrix factorisation [5,24] or high-order Taylor series has a better precision than the Euler method [25], we adopt the Euler method due to its merit of simplicity and sufficient precision at high sampling rate. At the kth instant, i d(k) , i q(k) and ω (k) are the sampled values, R, L d , L q , l f are the system parameters.…”
Section: Predictive Model Under Synchronous D-q Framementioning
confidence: 99%
“…To predict the future states of the system, forward Euler discretisation (2) is applied to (1) to obtain the discrete predictive model (3) around the k th instant as followsnormaldinormaldt(i(k+1)i(k))Tnormals{idfalse(k+1false)P=idfalse(kfalse)+false(udfalse(kfalse)Ridfalse(kfalse)+ωfalse(kfalse)Lqiqfalse(kfalse)false)×Ts/Ldiqfalse(k+1false)P=iqfalse(kfalse)+false(uqfalse(kfalse)Riqfalse(kfalse)ωfalse(kfalse)Ldidfalse(kfalse)ωfalse(kfalse)λffalse)×Ts/Lqwhere the superscript ‘P’ denotes the predicted quantities and T s is the sampling interval. Although the zero‐order‐hold discretisation approximated by matrix factorisation [5, 24] or high‐order Taylor series has a better precision than the Euler method [25], we adopt the Euler method due to its merit of simplicity and sufficient precision at high sampling rate.…”
Section: C‐mpc For Ipmsm Drivesmentioning
confidence: 99%